Peran ayah terhadap kepercayaan diri pada dewasa awal - Fadhilah, Asma'; Pratiwi, Rahmawati; Hamka (Fakultas Psikologi Universitas Hang Tuah, 2026)
Early adulthood is a developmental phase that presents various demands, making self-confidence an important psychological aspect. The role of the father is one factor that shapes self-confidence. However, the burden of caregiving duties often lays on mothers, so fathers are often less actively involved in childcare. This study aimed to determine the role of the father on self-confidence in early adulthood. A survey method with accidental sampling was used, involving 350 early adult respondents aged 18-25 years old, and using father’s role scale and self-confidence scale. Data analysis using simple linear regression showed the influence of father’s role on self-confidence in early adulthood. It also showed that father’s role contributed 5.6% to self-confidence of early adults. This could be concluded that the role of father, even though small, could be a contributing factor to determine self-confidence, supported by other psychological factors.